from the history of dwelling - Lidin, Konstantin (project baikal, 2026)
Dwelling accompanies human beings throughout their history. As a matter of fact, dwelling facilities appeared much earlier than humans: many creatures living on Earth build their nests, which are sometimes very ingenious. But only a human dwelling bears the imprint of a lifestyle that is infinitely diverse among people. Today, ancient residential buildings tell us stories about how our ancestors lived, what value system they adhered to, what they considered beautiful and what they considered shameful. The history of dwelling is the most complete, ancient and continuous collection of narratives about the past of peoples. Our collection contains several examples of what the dwelling can tell the current generation and future generations about the past life, without which, however, there is no future.